Perbandingan Risiko Produksi dan Pendapatan Usahatani Padi Sawah Tadah Hujan Berdasarkan Status Kepemilikan Lahan (Studi Kasus di Desa Kanaungan Kecamatan Labakkang Kabupaten Pangkep) - Amir Amir; Arifin Arifin; Abd. Asis Pata (Jurnal Agribis, 2022)
This research was conducted in Desas Kanaungan, Labakkang District, Pangkep Regency. This location was chosen with the consideration that the farmers cultivate rainfed lowland rice and are easy to access because the distance is not far. There are two data used, namely: primary data, namely data collected directly by researchers with observations through direct interviews and also through the help of a list of questionnaires and secondary data, namely data obtained from literature studies with various sources that can be used as references in this study. The aims of this study were: to determine the risk of production and income of rainfed lowland rice farming based on land ownership status in Kanaungan Village, Labakkang District, Pangkep Regency and to determine the magnitude of the difference in production risk and income of rainfed lowland rice farming based on land ownership status in Kanaungan Village, Labakkng District, Pangkep Regency. Data were collected from survey results using a questionnaire and added with field observations. Data processing is done by using tabulations and percentages. The analysis used is descriptive quantitative analysis method to determine the risk of production and income of rainfed lowland rice farming based on land ownership status in Kanaungan Village, Labakkng District, Pangkep Regency. The results showed that the production risk of farmers with a Coefficient of Variation (KV) was 1.144 and non-owners a Coefficient of Variation (KV) was 0.566. while the income risk of farmers with the Coefficient of Variation (KV) is 1.089 and non-owners the Coefficient of Variation (KV) is 0.662.